A Clinical Survey to Evaluate the Patients and Dentists perspective on Denture Cleansing Habits in Mumbai and Navi Mumbai (Global Journal of Medical Research, 2014)
This study was performed to evaluate the patients and dentists perspective on denture cleansing habits. Using a prepared questionnnaire a total of 100 patients and 100 practicising dentists living in Mumbai and Navi Mumbai were surveyed, regarding their opinions and views about denture hygiene and cleansing routines. The conclusions drawn from the study, were that most of the denture wearers did not clean their dentures satisfactorily and the dentists did not provide complete information about denture cleanliness to their patients.
Keywords: denture cleansing; denture hygiene; oral health; cleansing agents; mechanical methods; professional cleansing; denture care negligence; denture staini